PROFILE OF THE MOTOR PERFORMANCE OF THE PARTIPANTS OF XXIV SCHOOL GAMES OF SANTA CATARINA. (Fiep Bulletin - online, 2014)
The objective of this study was to analyze the motor performance of the participants of 24th School Games of Santa Catarina, from 11 to 14 years old, as well as to compare them with studies accomplished in the state of Santa Catarina - SC (FAGUNDES, 2005) and in Rio Grande do Sul - RS (LORENZI et al., 2005). The sample was composed by 416 scholars being 218 male (52,4%) and 198 female (47,6%), competing in the modalities of volleyball (n=146, being 79 boys and 67 girls), basketball (n=111, being 69 boys and 42 girls), handball (n=96, being 31 boys and 65 girls) and football indoor (n=63, being 39 boys and 24 girls). The battery of tests used was developed by Sport Brazil Project (PROESP-BR). The analysis of the data was accomplished through the descriptive statistics (average, standard deviation and frequency) and the test student "t" for independent samples. The ages were 13,22±0,88 years old and 13,10±0,88 years old; the weight was 52,74±10,5kg and 50,94±8,9kg; the stature was respectively 164,46±10,2cm and 161,44±7,4cm and the span 168,70±11,8cm and 163,17±13,4cm for the boys and the girls. In relation to the motor performance an increment was observed in all the variables with the passing of the years in both sexes, it was notable the obtaining of superior results by the boys in all the variables (p
Keywords: adolescents; sport; motor performance